Questionnaire Survey를 이용한 말의 품성 평가 - 김남영; 박용상; 고문석; 조원모; 조인철; 홍현주; 박지윤; 정광연; 조상래 (Journal of animal reproduction & biotechnology (Online), 2013)
The objective of the study is to assess temperament of a horse based on general temperament test by a questionnaire survey. Five test criteria were identified: gentleness, patience, aggressiveness, sensitivity, and friendliness, each on a 5-point scale. 114 horses bred at the National Institute of Animal Science (NIAS) in 2010, 2011 and 2012. The horses recorded scores of 3.6∼3.9 for gentleness, 3.1∼3.6 for patience, 3.4∼4.0 for aggressiveness, 2.8∼3.2 for sensitivity,and 3.4∼3.8 for friendliness, the overall score for sensitivity the lowest. Horses born in 2012 scored lower than the rest in all five areas at a statistically significant level (P<0.05). By gender, the colts scored higher than the fillies in all five areas, but the discrepancy was not statistically significant. Factor analysis yielded only one factor, and the Cronbach's α value was 0.980 for standardization of Factor 1, indicating a high reliability of internal consistency. The correlation coefficients among the test criteria ranged between 0.85 and 0.91 (P<0.01). The assessment criteria used in this study are expected to provide a useful basis designing a temperament test horses. KCI Citation Count: 1